Determinación de Microfilariasis en caninos (Canis lupus familiaris) atendidos en el centro Veterinario DR JEFF, Cantón Ventanas, Provincia de Los Ríos - Quintanilla Yanez, María de los Ángeles (2025)
This titling project focused on the determination of Microfilariasis in canines at the DR. JEVER Veterinary Center, located in the canton of Ventanas, Ecuador. This pathology, caused by the parasite Dirofilaria immitis, is a zoonotic disease that can be asymptomatic in dogs, but has serious implications for public health. The main objective was to diagnose the presence of Microfilariae immitis in canines, evaluating factors such as the age, sex and breed of the affected animals. The methodology of the study was descriptive, using an inductive-deductive and experimental-descriptive approach. Diagnostic tests, such as the Woo Test, were performed and statistical analyses were applied to determine the prevalence of the disease in the dog population. In addition, data collection was carried out through fieldwork, which includes tabulation of results. Two positive cases of Microfilariasis were obtained, representing 4% of the total sample evaluated. Of these cases, one was male (1/24) and the other female (1/26). Therefore, one belonged to the young group between 1 and 2 years of age and the other to the adult group of 2 to 3 years of age. In terms of breed, mixed-breed dogs presented one positive case, representing 50% of the total parasitosis detected. In contrast, the Pitbull breed also showed a low prevalence, with only one positive case (50%). Therefore, the study contributes to the knowledge about Microfilariasis in canines and its impact on public health, through a rigorous and ethical methodological approach.